Biochemical Studies on Adenovirus Multiplication, XIX. Resolution of Late Viral RNA Species in the Nucleus and Cytoplasm - Parsons, J. Thomas (1971)
Late after infection of cultured human cells (KB) with adenovirus type 2, the nucleus contains heterogeneous viral RNA species ranging in size from 10 to 43 S. Four viral RNA species found in the nucleus (36, 38, 40, and 43 S) are synthesized predominantly during a 15-min labeling period with [(3)H]uridine, while smaller RNA species accumulate when labeling is continued for longer periods. In contrast, 6-8 viral RNA species, of sedimentation coefficient from 10 to 29 S, are found in the cytoplasm after a 30-min pulse label and a 2-hr chase. DNA-RNA hybridization-competition experiments demonstrate that viral RNA sequences present in nuclear 36-43S RNA are also present in cytoplasmic and polyribosomal RNA, suggesting that at least some of the cytoplasmic viral-specific RNA molecules are derived by cleavage of high molecular weight precursors from the nucleus.